An empirical evaluation of the effectiveness of share recommendations by stockbrokers and investment advisory services in South Africa - N. Bhana (South African Journal of Business Management, 1990)
The objective of this study is to determine if the buy and sell recommendations of stockbroker and investment advisory services have provided clients with superior returns during the period 1979-88. Superior returns were associated primarily with buy, rather than sell, recommendations. The recommendations were associated with genuine changes in the value of securities and were not mere self-fulfilling prophecies. The apparent ability of stockbrokers/investment advisory services to offer their clients superior investment recommendations may be due to their superior access to new information which they process more quickly and efficiently than most investors. Investment analysts also appear to have a potential for acquiring inside information and this in turn may have contributed to their superior returns.
Keywords: 650